Foreign Affairs: an American quarterly review (New York Council On Foreign Relations, 1974)
“The articles in Foreign Affairs will deal with questions of international interest today. They will cover a broad range of subjects, not only political but historical and economic.
Keywords: International relations; INTERNATIONAL RELATIONS; POLITICAL CONDITIONS; ECONOMIC CONDITIONS; USA; AMERICAN HISTORY; PERIODICALS